A game-free microfoundation of mutual optimism - Marco Serena (Games, 2019)
One of the most widely accepted explanations for why wars occur despite its Pareto-suboptimality is mutual optimism: if both sides expect to gain a lot by fighting, war becomes inevitable. The literature on mutual optimism typically assumes mutually optimistic beliefs and shows that, under such an assumption, war may occur despite its Pareto-suboptimality. In a war-peace model, we show that, if players neglect the correlation between other players' actions and their types-a well-established concept in economics-then players' expected payoffs from war increase relative to conventional informational sophistication predictions, hence providing a microfoundation of mutual optimism.
Keywords: 330; correlation neglect; incentives to go to war; information; mutual optimism